The terror management effects of a disaster song. (January 2020) - Higgins, Laura; MacIntyre, Peter D.; Ross, Jessica; Sparling, Heather
Following terror management theory (TMT), we hypothesized that listening to a disaster song could increase cultural worldview defenses in a manner similar to the mortality-stimulating essay typically used in TMT research. Participants were divided into four groups. Two of the groups received death-related themes: one wrote an essay about dying and the other group heard a song about men who died in a shipwreck. The other two groups received pain-related stimuli: one wrote an essay about dental pain and the other heard a song about a migrant worker's painful separation from family. Dependent variables examined pro-social behavior, ranking one's country, children, and emotions. Results showed similar effects for the mortality-stimulating essay and the disaster song on two variables: ranking one's country in the world and the importance of having children. In addition, compared to the pain-of-separation song, the disaster song produced significantly more negative and less positive emotion ratings; the emotion ratings of the essay groups did not differ significantly. Results show that a disaster song can produce effects similar to those that have been observed for a mortality-stimulating essay. Further, the effects of disaster songs may extend to strengthening cultural worldview defenses.